Exploring the usage of twitter in higher education - Faerozh Madli; Yuzainy Janin; Ang, Hong Loong; Wong, Sing Yun; Toh, Pei Sung (Human Resource Management Academic Research Society (HRMARS), 2023)
The use of technology in the context of higher education is not a novel idea as lecturers and students have used different types of technology such as smartphones, software, and social media. In recent years, social media like Twitter have been extensively used to decimate information about learning. However, there is a global disparity between the use of social media sites like Twitter for higher education; some countries use it extensively, while for some, its use is a rarity. This situation is evident in Malaysia, where there is a low percentage of students and lecturers using Twitter in teaching and learning. Furthermore, there are limited studies related to Twitter in the context of higher education in Malaysia. Based on this gap, this study aims to devise a strategy for using Twitter in Malaysia’s higher education context. This study discusses some of the strategies that can be implemented in conducting learning inside or outside the class. In addition, the study’s findings can benefit many education stakeholders by exploring ways to optimise the use of Twitter in Higher Education Institutions (HEIs).